2013
DOI: 10.1002/ajim.22246
|View full text |Cite
|
Sign up to set email alerts
|

Changes in psychosocial work environment and depressive symptoms: A prospective study in junior physicians

Abstract: Negative changes in the psychosocial work environment, specifically increased ERI, are associated with depressive symptoms in German junior physicians. Reducing the non-reciprocity of working life, particularly improving reward at work, may have beneficial effects on prevention of mental health problems in the hospital workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 48 publications
0
18
0
3
Order By: Relevance
“…We observed that increased work stress was linked to higher levels of burnout, particularly to emotional exhaustion [10]. While prospective evidence on the impact of work stress on burnout in pediatricians is not available to date, similar studies in other medical specialties corroborate the impact of effort-reward imbalance and elevated risks of mental disorders and poor functioning at work [11]. Thus, promoting wellbeing of pediatricians includes reduction of the burden of psychosocial stress at work.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…We observed that increased work stress was linked to higher levels of burnout, particularly to emotional exhaustion [10]. While prospective evidence on the impact of work stress on burnout in pediatricians is not available to date, similar studies in other medical specialties corroborate the impact of effort-reward imbalance and elevated risks of mental disorders and poor functioning at work [11]. Thus, promoting wellbeing of pediatricians includes reduction of the burden of psychosocial stress at work.…”
Section: Discussionmentioning
confidence: 52%
“…We suggest system-based, i.e., organizational and work-design interventions that address the reciprocity of effort and reward in the workplace. This is of particular interest within the clinical context, where high job demands and detrimental working conditions lead to increasing resignation in physicians and jeopardize patient safety [8,24,11,12]. This could be achieved through reducing effort and work demands, while simultaneously improving reward in the hospital workplace.…”
Section: Implications Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…[26][27][28] A high overcommitment (OC) score and a high ERI score are associated with depression [29][30][31] and anxiety, 32 which both can influence negatively the course of IBD as delineated above.…”
mentioning
confidence: 99%